The Role of Government Policy, Technology Adoption, and Rural Entrepreneurship in Enhancing Economic Development in Villages in Indonesia - Haryono, Haryono (Westscience Press, 2025)
This study examines the roles of government policy, technology adoption, and rural entrepreneurship in enhancing economic development in Indonesian villages. Using a quantitative approach, data were collected from 200 respondents through a structured questionnaire employing a 5-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to test the hypothesized relationships. Results indicate that government policy significantly influences technology adoption, rural entrepreneurship, and economic development. Technology adoption positively affects both rural entrepreneurship and economic development, while rural entrepreneurship strongly drives economic development and partially mediates the effect of technology adoption on economic outcomes. These findings highlight the importance of integrated interventions that combine supportive policies, technological empowerment, and entrepreneurial initiatives to foster sustainable rural growth. The study provides practical insights for policymakers, development practitioners, and village leaders aiming to enhance the socio-economic well-being of rural communities.